Различные модели организации арт-резиденций в Украине - Белявцева, О.О. (Культура народов Причерноморья, 2013)
В статье рассматриваются модели арт-резиденций, получившие распространение в нашей
стране. Цель данной работы – выявление характерных особенностей украинских резиденций. Изучая
становление этого явления, мы обращаемся к подобной зарубежной практике, а также к деятельности
советских Домов творчества как организаций, похожих по многим параметрам на современные
отечественные арт-резиденции и оказавших влияние на их формирование в постсоветской Украине. У статті розглядаються моделі арт-резиденцій, які набули поширення в нашій країні.
Метою роботи, що пропонується, є виявлення характерних особливостей українських резиденцій. При
вивченні становлення цього явища, ми звертаємося до подібної закордонної практиці, а також до
діяльності радянських Будинків творчості як організацій, схожих за багатьма параметрами на сучасні
вітчизняні арт-резиденції та вплинувших на їх формування у пострадянській Україні. The article is devoted to the models of art residences, which widely spread in our country. The aim of
this work is to reveal the characteristic features of Ukrainian residences. Studying the making of the
phenomenon we appeal to foreign practice as well as to the activity of Soviet Creativity Houses as organizations
that were close in some parameters to modern residences and influenced much their forming in post-Soviet
Ukraine. There are large, prestigious residences and small amateur ones. In some residences artists collaborate
within a joint project, in others – prepare works to exhibitions, in the third – meet together to exchange their
experience and ideas. Some Ukrainian residences are organized in the places that are popular among several
generations of the creative intelligentsia. Art residences promote the favourable image of the region where they
take place, cause the transformation of the industrial areas to the cultural space and attract the men of art from
different countries.